Effect of Preparation Methods on the Physicochemical Properties and Bacterial Community of Chixiangxing Baijiu Qu - WANG Yuliang, LI Zhipu, SU Zejia, LIANG Jinglong, BAI Weidong, FEI Yongtao, ZHAO Wenhong, FANG Yifei (Shipin Kexue, 2023)
The dynamic changes of moisture, acidity, amino nitrogen content, fermentation power, esterification power, liquefaction power, saccharification power and acid protease activity were measured during the traditional and mechanized production of Chixiangxing Baijiu Qu, the structural characteristics of bacterial communities were analyzed by high-throughput sequencing technology, and the correlations among bacterial communities and those between them and physicochemical factors were predicted by Pearson’s statistical method. The results showed that moisture content, amino nitrogen content, saccharifying power, esterification power and fermentation power were significantly higher and acidity was significantly lower at the end of the traditional fermentation process than mechanized fermentation. However, there was no significant difference in liquefaction power or acid protease activity between the two fermentation processes. A total of 18 bacterial genera with relative abundance greater than 1% were identified during traditional and mechanical fermentation, including Lactobacillus, Bacillus, Pediococcus, Weissella, Ralstonia, Leuconostoc, Acetobacter, Exiguobacterium Staphylococcus, Kurthia, Acinetobacter, Enterococcus, Glutamicibacter, Thermobifida, Streptomyces, Enterobacter, Gemmobacter, and Oceanobacillus, among which Lactobacillus, Bacillus, Pediococcus and Weissella were the core ones for both traditional and mechanical fermentation, but their proportions were significantly different between the two fermentation processes. Bacillus was dominant in mechanized fermentation and its abundance was significantly higher in mechanized than traditional fermentation, while Lactobacillus was dominant in traditional fermentation; its abundance was significantly higher in traditional than mechanical fermentation, and so was the abundance of Pediococcus and Weissella. The correlation analysis revealed that Bacillus was in competition with Lactobacillus; Pediococcus and Weissella, and Lactobacillus were positively correlated with amino nitrogen content, fermentation power, esterification power, saccharifying power and acid protease activity, and Bacillus was positively correlated with acidity, amino nitrogen content and liquefaction power. Moreover, there were differences in the texture of traditional and mechanized Qu samples and the amount of oxygen in contact with Qu during the making process, which may be related to the addition of wheat bran in the mechanized process and the environmental difference between the two processes. Appropriate control of environmental oxygen concentration and stabilization of environmental changes in the mechanized process can be conducive to the balanced growth of core functional aerobic and anaerobic microorganisms, thereby improving Qu quality. This study provides a scientific theoretical basis for advancing the development of the mechanized fermentation of Chixiangxing Baijiu Qu.